Analysis of benthic macroinvertebrates and biotic indices to evaluate water quality in Sardina´s river, Ecuadorian Chocó Andino - Machado, Verónica; Granda, Roberto; Endara González, Alexandra (Enfoque UTE, 2018)
An aquatic macroinvertebrates community analysis was made at Sardinas River, in the rainy and wet seasons of 2018, using macroinvertebrates as environmental bioindicators; these were collected with Surber net and hand collection, in five points along the river. In the laboratory they were classified and identified as class, order and family. They were studied by the analysis of richness (S) and abundance (N). The environmental quality was determinate applying the BMWP/Col and EPT indices. A total of 526 individuals belonging to 15 orders and 44 families were collected. 35 in the rainy season and 31 in the dry season. The most abundant family in rainy season was Leptophlebiidae, 34 specimens (12.8%). In dry season, the most representative was Chironomidae with 45 individuals (17.2%). In rainy season the point 2 had greater richness S16 and in the dry season P1, S18. P3 - P5 presented medium quality water (BMWP/Col = 69-94 and an EPT average of 47.05%). This study determined through BMWP/Col and EPT indices, in association with the taxa collected and the calculations of (S), (N) and relative abundance (%), the ecological status of the studies’ area.